Why did adolescents have sleep problems after earthquakes? Understanding the role of traumatic exposure, fear, and PTSD. Issue 3 (June 2017) - Zhou, Xiao; Wu, Xinchun; Chen, Qiuyan; Zhen, Rui
Abstract : To examine the relationships between trauma exposure, fear, post‐traumatic stress disorder, and sleep problems in adolescents, 746 adolescent survivors of the 2008 Wenchuan earthquake in China were assessed at 1 year (T1) and 1.5 years (T2) after the earthquake using a trauma exposure questionnaire, a fear questionnaire, a child posttraumatic stress disorder symptom scale, and a subscale on child sleep problems. The results showed that T1 trauma exposure were not directly associated with sleep problems at T1 and T2, but played a positive role in sleep problems at both T1 and T2 indirectly through T1 posttraumatic stress disorder and T1 fear. T1 trauma exposure was also positively and indirectly associated with T2 sleep problems through T1 posttraumatic stress disorder via T1 sleep problems, or through T1 fear via the path from T1 posttraumatic stress disorder to T1 sleep problems. These findings indicated that fear and posttraumatic stress disorder 1 year after the earthquake played a mediating role in the relationship between trauma exposure at 1 year after the earthquake, and sleep problems at both 1 year and 1.5 years after the earthquake, respectively. In particular, posttraumatic stress disorder also had a multiple mediating effect in the path from trauma exposure to sleep problems via fear. Furthermore, the findings indicated that sleep problems were relatively stable between 1 and 1.5 years after an earthquake.